Lack of TNFRI signaling enhances annexin A1 biological activity in intestinal inflammation - Sena, Angela (2015)
We evaluated whether the lack of TNF-α signaling increases mucosal levels of annexin A1 (AnxA1); the hypothesis stems from previous findings showing that TNF-α neutralization in Crohn´s disease patients up-regulates systemic AnxA1 expression. Biopsies from healthy volunteers and patients under anti-TNF-α therapy with remittent ulcerative colitis (UC) showed higher AnxA1 expression than those with active disease. We also evaluated dextran sulfate sodium (DSS)-acute colitis in TNF-α receptor 1 KO (TNFR1-/-) strain with impaired TNF-α signaling and C57BL/6 (WT) mice. Although both strains developed colitis, TNFR1-/- mice showed early clinical recovery, lower myeloperoxidase (MPO) activity and milder histopathological alterations. Colonic epithelium from control and DSS-treated TNFR1-/- mice showed intense AnxA1 expression and AnxA1+ CD4+ and CD8+ T cells were more frequent in TNFR1-/- animals, suggesting an extra supply of AnxA1. The pan antagonist of AnxA1 receptors exacerbated the colitis outcome in TNFR1-/- mice, supporting the pivotal role of AnxA1 in the early recovery. Our findings demonstrate that the TNF-α signaling reduction favors the expression and biological activity of AnxA1 in inflamed intestinal mucosa.